IMPORTANCE OF MICROCALCIFICATIONS IN MAMMOGRAPHIC DIFFERENTIATION OF THE INVASIVE DUCTAL BREAST CANCER AND OF THE DUCTAL CARCINOMA IN SITU - Šarac, Vanja; Nadrljanski, Mirjan (Medicinski podmladak, 2017)
Abstract Introduction: Microcalcifications represent a significan tand reliable sign of the presence of the malignant breast lesion. Aim: The aim of the paper is to radiologically evaluate the type and distribution of suspicious microcalcifications in patients with invasive ductal carcinoma (IDC) and ductal carcinoma in situ (DCIS). Material and Methods: Retrospective analysis includes the evaluation of the type and distribution of suspicious microcalcifications in patients with histologically verified malignant lesions: invasive ductal carcinoma (N1=40 pts.) and ductal carcinoma in situ (N2=40 pts.). Standardised mediolateral oblique and cranicaudal views were selected for the evaluation of the images taken onthe full-field digital mammograph (FFDM «Selenia», Institute of Oncology and Radiology of Serbia, Belgrade), on the dedicated workstation of the mammography unit, with the aid of the software for lesion evaluation. Results: Eight patients with invasive ductal carcinoma (20%) had no suspicious microcalcifications, as opposed to the patients with ductal in situ carcinoma where all patients had suspicious microcalcifications (p